2020
DOI: 10.12911/22998993/118299
|View full text |Cite
|
Sign up to set email alerts
|

Features of Heavy Metals Accumulation in Bottom Sediments of the Southern Bug Hydroecosystem

Abstract: The performed studies allowed determining the peculiarities of heavy metals accumulation in the sediments, as well as the nature of their distribution in the hydroecosystem Southern Bug (Ukraine). Geochemical anomalies are formed in the zones of influence of industrial and urban agglomerations. Technogenic pollutions of bottom sediments with heavy metals affects the qualitative state of the water environment and can cause cumulative toxicosis on the hydrobiont population in the zones of geochemical anomalies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The pollution of the Black Sea with metals is a major environmental challenge (Strezov 2008). Metal elements are introduced into the marine environment by natural geological processes, rivers or direct discharge of industrial waste (Mitryasova et al 2020). Recent studies have revealed variable average concentrations of metals in seawater and surface sediments from the Bulgarian Black Sea coastal zone and pollution hotspots were designated (Peycheva et al 2017;Doncheva et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The pollution of the Black Sea with metals is a major environmental challenge (Strezov 2008). Metal elements are introduced into the marine environment by natural geological processes, rivers or direct discharge of industrial waste (Mitryasova et al 2020). Recent studies have revealed variable average concentrations of metals in seawater and surface sediments from the Bulgarian Black Sea coastal zone and pollution hotspots were designated (Peycheva et al 2017;Doncheva et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Under the conditions of the modern development of production, with a constant decrease in resources, there is a need for optimization of differences in technological process requirements and supporting resources environmental security. On the way to the sustainable development of production and technological processes, it is necessary to find innovative ways to improve the environmental performance of production processes and products (Ishchenko et al, 2017;Kardasz et al, 2018;Pohrebennyk et al, 2016;Mitryasova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The search for the methods to intensify the release of natural substances of different structural organization for comprehensive practical application on the principles of green chemistry, along with finding new and improving the already known methods of synthesis is an urgent task of both applied and fundamental sciences. At the base of modern green technologies, which are aimed at achieving zero waste, reducing energy costs, are the principles of sustainable development (Ishchenko and et al, 2019;Mariychuk et al, 2020a;Mitryasova et al, , 2020Bezsonov et al 2017;Pohrebennyk et al, 2016). Evaluation of the environmental impact of a chemical process requires the consideration of numerous factors, such as processing efficiency, safety, and cost effectiveness (Eissen, 2012;Hutchison, 2019;Petrov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%